The regulation of complementary and alternative medicine professions in Ontario, Canada - Jeremy Y. Ng (Integrative Medicine Research)
Background: This paper explains the regulation of complementary and alternative medicine (CAM) health professions, through the comparison of four distinct examples in Ontario, Canada including: chiropractors, naturopaths, homeopaths, and traditional Chinese medicine (TCM) practitioners. Methods: This study analyzes the agenda setting and formulation stage of the policy process. In other words, it explores what happened between stakeholders before each of these CAM professions achieved regulation. Alford’s model of dominant, challenging and repressed structured interests (DSIs, CSIs, and RSIs respectively) is used to describe the competition between various players within the healthcare system and their position in the health policy process. Results: All four CAM professions have existed as a RSI at some point in their history, however, over the last century has sought to align themselves with various (or even become) challenging structural interests (CSIs) in order to be recognized as a regulated health profession. Dominant structural interests (DSIs), particularly the medical profession, initially largely ignored these professions’ practices, unless sufficient public support of CAM practitioners’ therapies warranted them to consider the need to regulate them. Conclusion: Unregulated CAM professions may increase their likelihood of becoming regulated if they: (1) gain popularity/strong support from patients or the general public, (2) organize themselves sufficiently that they pose a direct threat to one or more scopes of practice desirable by the DSIs and/or (3) are willing to adopt standards in education, training, and ethics that may [initially] reduce their scope of practice or profession’s membership or slow their profession’s growth. Keywords: Complementary and alternative medicine, Professional regulation, Unregulated profession